The Effect of Mulched Ridge and Furrow Micro Catchment Water Harvesting on Red Pepper Yield and Quality Features in Bafra Plain of Northern Turkey - Yildirim, Demet; Cemek, Bilal; Unlukara, Ali (Elsevier, 2022)
For two decades, promising results have been obtained by ridge-furrow rainwater harvesting systems (RWHS) to feed the increasing world population and cope with water scarcity and drought in semiarid and arid areas. A two-year study in Turkey's semi-humid Black Sea Region was conducted to examine RWHS's effects on harvested water, soil water content, red pepper growth, yield, quality attributes, water consumption, and crop water productivity (WPc), crop water stress index (CWSI). The profitability of the system was examined by economic analysis. For these purposes, three different polyethylene-covered ridge widths (RWHS1: 100 cm, RWHS2: 120 cm, and RWHS3: 140 cm) were considered. To allow the harvested water infiltration root zone and grow red pepper, 80 cm width furrow areas with double plant rows were left between the covered ridges on contours. To compare the RWHS treatments, three conventional rainfed farming or dry farming treatments (DFS1, DFS2, and DFS3) with 90 cm, 100 cm, and 110 cm plant row distances were considered. Each treatment was replicated three times in the randomized block design experiment. Besides, a multiple regression model was developed to estimate the runoff from the plastic-covered ridges by using independent parameters such as covered ridge ratios and rainfall amounts (R-2 = 0.97). The red pepper consumed between 165 and 174 mm water in 2017 and 118-147 mm in 2018. Maximum red pepper yields, which increased by 68% in 2017 and 149% in 2018, were derived from RWHS1 as 33.2 and 27.19 t ha(- 1), respectively. As plastic-covered ridge width increased, red pepper yield decreased because of lowering plant density. RWHS improved red pepper yield and significantly increased leaf area, plant height, fruit length, and diameter. RWHS produced Turkey's highest red pepper WPc ratios, and RWHS1 improved WPc by 74% in 2017 and 169% in 2018. Although the red pepper consumed nearly the same amount of water under whole treatments, CWSI was lower under RWHS treatments. It was determined that sustainable red pepper farming according to the net income values under rainfed farmland in the region would not be possible without using rainwater harvesting systems such as RWHS1.
Keywords: Ridge-Furrow Ratio; Precipitation; Micro-Catchment Water Harvesting; Red Pepper; Semi-Humid Region